"Base Genep" Instant Spices Quality For Sale In East Denpasar - Sofia nggoweng; Ni Made Ayu Suardani singapurwa; I Nyoman Rudianta (SEAS (Sustainable Environment Agricultural Science), 2020)
Instant spices is a mixture of several spices that are young to be found in the market at an affordable price, and are usually used immediately as a cooking spice for certain foods. This study aims to determine the quality of the "Base Genep" instant spices sold in the East Denpasar Market. This research is a descriptive study using survey and experimental methods in the laboratory. The number of samples to be studied was 44 samples from 81 populations. The variables in the study were moisture content, pH, Escherichia coli, Total Plate Count (TPC) and mold. The results showed that from 44 samples of "Basa Genep" instant seasoning water content test results obtained were 21.62% - 23.707%, while the pH value of 44 samples of "Basa Genep" instant spice was obtained between 2.2-2.5 so that it meets the requirements.